Collective intelligence in financial knowledge management, Challenges in the information explosion era - Andres, Frederic; Rajkumar, Kannan (Inteligencja społeczności w finansowych systemach zarządzania wiedzą: wyzwania w dobie eksplozji informacji, 2011)
The emerging e-finance and the explosion of financial information impacted the evolution of finance information systems. With conventional techniques, it is hard to find a way to build a self-sustainable financial knowledge-based community. In order to achieve global semantic interoperability among financial information systems, semantic concepts are applied to build financial knowledge-based communities to deliver more robust, user friendly financial information search interfaces customized based on semantics. The key challenge is the integration between collective intelligence and financial knowledge management systems.It would enable to classify the most preferable terms that shared among the financial knowledge-based community. With this system, we will easily be able to identify financial information and collect finance vocabulary
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 22-33
Keywords: collective intelligence; finance semantics; knowledge management; Web 2.0; web 3.0; inteligencja społeczności; semantyka finansów; zarządzanie wiedzą